PENGHENTIAN PERKARA BERDASARKAN KEADILAN RESTORATIF DI KEJAKSAAN NEGERI GOWA : (Studi Siyasah Syar'iyyah) - Nurpaidah,; Jafar, Usman; Mustarin, Basyirah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to find out how the concept of Case Termination Based on Restorative Justice at the Gowa District Attorney's Office (Siyasah Syar'iyyah Study). The main problem is divided into several sub-problems, namely: How to stop cases based on restorative justice at the Gowa State Prosecutor's Office, What are the forms of cases related to restorative justice, and what is the siyasa syariyyah perspective on ending cases based on restorative justice. The research method used is data collection in the form of observation, interviews, documentation and reference tracing. The results of this study indicate that the implementation of restorative justice focuses more on conditions for creating justice and balance for the perpetrators of criminal acts and their victims themselves, and the perpetrators of criminal acts do not need to be sentenced to death but can be carried out with restorative justice efforts, in order to reduce the excess capacity of correctional institutions. or state prisons, restorative justice can also eliminate grudges for potential perpetrators of crimes so that they will not repeat their actions and can embrace and provide an understanding to the wider community about the dangers of committing a crime. In the perspective of siyasa syar'iyyah, termination of cases based on restorative justice can be carried out using the method of forgiving and paying diyat and law enforcers are not justified in acting arbitrarily in resolving cases, but must uphold justice in accordance with the regulations.